The relationship between tumor immunity and the cGAS-STING pathway in breast cancer: An immunohistochemical study - Haruto Nishida; Naoto Ohara; Ami Kato; Ryo Kaimori; Yoshihiko Kondo; Takahiro Kusaba; Hiroko Kadowaki; Kazuhiro Kawamura; Tsutomu Daa (Elsevier, 2024)
Breast cancer (BC) is classified into four major histological subtypes, namely luminal A, luminal B, HER2, and basal-like, and its treatment is based on these subtypes. The use of immune checkpoint inhibitors against BC depends on the expression of PD-1/PD-L1. Another tumor immune system-the cGAS-STING pathway-is a potential target for cancer immunotherapy. However, the status of the cGAS-STING pathway in BC has not been fully established. Therefore, we investigated the expression status of the cGAS-STING pathway and immune-related proteins in BC. We classified 111 BCs into six groups-29 hormone receptor-positive carcinomas, 12 HER2+ carcinomas (HER2), 8 luminal-HER2 carcinomas, 26 triple-negative breast carcinomas (TNBCs), 21 lobular carcinomas (LC), and 15 carcinomas with apocrine differentiation (CAD)-and investigated the relationship between BC and tumor immunity via the cGAS-STING pathway using histopathological and immunohistochemical methods. Expression of cGAS was high in CADs (100%) and low in TNBCs (35%); STING-positive lymphocytes were high in TNBC (85%, P = 0.0054). Expression of pSTAT3 was significantly high in patients with TNBC (≥10%, 88%). The proportion of PD-L1-positive tumor cells was higher in TNBCs (54%) than in other BCs (30%). SRGN expression was significantly higher in the TNBC group than in the other BC groups (58%). Tumor immune responses may differ among tumor subtypes. The cGAS-STING pathway may be functional in TNBC and CAD but not in LC. Therefore, targeting the cGAS-STING pathway might be useful in BC, particularly TNBC and CAD.